2008
DOI: 10.1158/0008-5472.can-08-0969
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Notch-1 and Notch-2 on Mesothelioma Cell Survival under Hypoxia Are Exerted through the Akt Pathway

Abstract: Malignant mesothelioma (MM) is a cancer of the lining of the lungs, heart, and intestine and is known to respond poorly to chemotherapy. Here we show

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 39 publications
(52 reference statements)
5
93
1
Order By: Relevance
“…It has been reported that cross-talk between Notch signaling and PI3K/Akt pathway could influence tumor progression (Kunnimalaiyaan and Chen, 2007;Meurette et al, 2009). Notch1 activation was reported to suppress the expression of PTEN, a key molecule in PI3K/Akt pathway, in T-ALL and mesothelioma cell (Palomero Graziani et al, 2008). There was also a report concerning the involvement of Notch1 in PTEN upregulation in human 293 cells (Whelan et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that cross-talk between Notch signaling and PI3K/Akt pathway could influence tumor progression (Kunnimalaiyaan and Chen, 2007;Meurette et al, 2009). Notch1 activation was reported to suppress the expression of PTEN, a key molecule in PI3K/Akt pathway, in T-ALL and mesothelioma cell (Palomero Graziani et al, 2008). There was also a report concerning the involvement of Notch1 in PTEN upregulation in human 293 cells (Whelan et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Notch2 has been shown to play a key role in the establishment and survival of the Sus cell population of the OE (60), but Notch1 does not. With respect to disease processes, it is known that Notch1 and Notch2 play opposite roles in oncogenesis and have been used as opposing cancer prognostication factors (61)(62)(63). Additionally, Notch1 and Notch2 play different roles in diabetic nephropathy (64).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations of Notch signaling that function in tumor initiation, progression, angiogenesis and metastasis have been found to be mediated through the activation of several important downstream pathways. Until now, b-catenin, 17 AKT, 32,33,38 Pin1, 39 Snail, 22 MMP9 19 and HES1 36 have been reported to either function as the downstream targets or be associated with Notch signaling in cancers. Notch signaling induces EMT Figure 4.…”
Section: Discussionmentioning
confidence: 99%